2021
DOI: 10.3390/agronomy11112174
|View full text |Cite
|
Sign up to set email alerts
|

Allelopathic Activity of Strigolactones on the Germination of Parasitic Plants and Arbuscular Mycorrhizal Fungi Growth

Abstract: Strigolactones (SLs) are a prime example of allelochemicals, promoting parasitic plant germination and certain hyphal branching factors associated to the growth of symbiotic arbuscular mycorrhizal fungi (AMF). However, the study of SLs is complex, and various issues have yet to be studied in depth. This review intends to provide an overview of the works that have been conducted on the identification, isolation, and evaluation of the allelopathic activity of natural canonical and non-canonical SLs on parasitic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 108 publications
0
7
0
Order By: Relevance
“…The availability of good quantities of EPYR will also allow us to perform ecotoxicological studies using organisms representing different trophic levels of aquatic and terrestrial ecosystems, namely, producers (e.g., the green freshwater alga Raphidocelis subcapitata and the macrophyte Lepidium sativum ), consumers (e.g., the water flea Daphnia magna and nematode Caenorhabditis elegans ), and decomposers (e.g., the bacterium Aliivibrio fischeri ) [ 16 ]. The development of rapid and sensitive methods for the quantification of EPYR in complex mixtures is needed for these purposes, as are the requirements for modern analysis, identification, and quantification of compounds in natural samples in general [ 17 , 18 ]. The quantification of specific bioactive compounds produced by microorganisms and plants is, in fact, a focus of attention in allelopathy studies [ 19 ], and, serving as a clear example, is the quantification study of the phytotoxin tenuazonic acid produced by P. oryzae [ 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…The availability of good quantities of EPYR will also allow us to perform ecotoxicological studies using organisms representing different trophic levels of aquatic and terrestrial ecosystems, namely, producers (e.g., the green freshwater alga Raphidocelis subcapitata and the macrophyte Lepidium sativum ), consumers (e.g., the water flea Daphnia magna and nematode Caenorhabditis elegans ), and decomposers (e.g., the bacterium Aliivibrio fischeri ) [ 16 ]. The development of rapid and sensitive methods for the quantification of EPYR in complex mixtures is needed for these purposes, as are the requirements for modern analysis, identification, and quantification of compounds in natural samples in general [ 17 , 18 ]. The quantification of specific bioactive compounds produced by microorganisms and plants is, in fact, a focus of attention in allelopathy studies [ 19 ], and, serving as a clear example, is the quantification study of the phytotoxin tenuazonic acid produced by P. oryzae [ 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…In broomrape species, strigolactones are the main class of germination stimulants, being characterized in more than twenty-five structural forms [ 13 , 14 ]. Strigolactones are exuded by crop roots to mediate plant-microbial beneficial interactions [ 14 , 15 ], and collaterally they are used by broomrape weeds to locate the crop root vulnerable to infection. Host-specific broomrapes respond to other chemical classes of germination stimulants.…”
Section: Introductionmentioning
confidence: 99%
“…The germination of broomrape seeds is commonly stimulated by specific compounds exuded by potential host plants in their surroundings. The family of phytohormones named strigolactones represents the most studied structures, though diverse sesquiterpene lactones produced by plants have been discovered as potent elicitors of germination of some broomrape species, being inactive on the germination of other broomrape species, with the case of costunolide and dehydrocostus lactone produced by sunflower being one of the most representative [ 10 , 23 ]. Thus, the study of sesquiterpene lactones also focused on the interest of parasitic weed research, covering topics like mechanisms, biosynthesis, and the use of materials for the development of bioactive derivatives against parasitic weeds [ 38 , 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…In the pursuit of sustainable methods to control broomrapes, great attention is directed towards studying plants whose extracts or specialized metabolites exhibit phytotoxicity or germination-inducing activity (suicidal germination) [ 10 , 11 , 12 ]. Recent studies have demonstrated positive outcomes with plants and their secondary metabolites by studying safflower ( Carthamus tinctorius ), maize ( Zea mays L.) or the invasive plant Conyza bonariensis [ 11 , 13 , 14 ] from this perspective.…”
Section: Introductionmentioning
confidence: 99%